Similarity coefficients influence the delimitation of species in the genus Aloe l. (Xanthorrhoeaceae) - Amir, Halima; Manoko, Mkabwa (Tanzania Journal of Science, 2021)
The present study was designed to establish the influence of coefficients indices in delimiting species using phenetic approach based on morphological data. Data were collected from thirty nine Aloe species described in Flora of Tropical East Africa. A total of forty two qualitative and quantitative characters were compiled from 83 specimens of aloes. Ten coefficient indices were tested. Data were analysed using UPMA approach of PAST software. The analyses confirmed that, truly coefficient of indices influenced the resulting classification. Of the 10 coefficients used only three produced 36-38 of the 39 species. Almost a third produced less than ten species-specific clusters another third producing less than 25 species–specific clusters. The best coefficients were Gower, Hamming and Rho whereas Chord, Correlation and Euclidean were the worst. These findings are comparable to other similar studies. Key words: Phenetics, morphological characteristics, cluster analysis, coefficient index, phenogram, Aloe